CRIMINAL OFFENSE PERSECUTION BY FOOTBALL PLAYERS IN THE PSSI REGIONAL COMPETITION: JURIDICAL REVIEW - Bambang Irianto; Andy Prasetyo; Suwarno (SYNTIFIC, 2023)
Background. Football is the most popular sport in the world. Football cannot be seen as just a sporting game that relies on physicality alone, but in the game of football emotions, adrenaline, passion, pride, and dedication are in it. Because of this, in a football match, physical contact cannot be avoided, ranging from light, moderate to heavy physical contact. So that football players have a tendency to commit violence against the body, which is prohibited in national law contained in Article 351 of the Criminal Code concerning persecution. The purpose of this study was to explain the criminal offense of persecution by football players in the PSSI regional competition. Research Method. This research was normative legal research with a juridical review approach, using legal rules, books and journals related to the research problem. Findings. Football has its law, namely the FIFA legal system which is transnational. In the FIFA legal system is divided into two namely Lex Sportiva & Lex Ludica. FIFA as an international football organization prohibits all forms of intervention in the realm of football. Conclusion. The state in enforcing state law must of course be careful not to be interpreted as a form of intervention by the state and violate the FIFA legal system.